Quality improvement intervention for school-based support teams for adolescents’ mental health in selected secondary schools in Gauteng: A study protocol - Xolelwa Dyani; Olanrewaju Oladimeji; Moreoagae Bertha Randa (PLoS ONE, 2026)
The prevalence of mental health disorders among adolescents poses a significant global health challenge, with approximately one in seven individuals aged 10–19 affected. The limited access to effective mental health services worsens this issue, particularly within schools, which are critical settings for early intervention. The study aims to develop and implement a school-based support team improvement intervention to enhance the mental health of adolescent learners in secondary schools. This study will employ a sequential explanatory mixed-methods approach design. The research will be conducted at selected secondary schools, and the participants for the study will be adolescents aged 13–19 and members of the school-based support team (SBST). Questionnaires will be administered to learners to determine the prevalence of common mental health challenges among adolescents and to determine the factors associated with mental health challenges among adolescents. A scoping review will also be conducted to examine existing interventions aimed at supporting learners with mental health challenges. Following the quantitative phase, interviews will be conducted with SBST members to explore the challenges and successes in supporting learners with mental health problems. The second phase will involve the development and implementation of the SBST quality-improvement intervention to support adolescents experiencing mental health challenges in secondary schools. The researcher will use Statistical Package for the Social Sciences (SPSS, 30.0.0) for quantitative data analysis and statistical interpretation. In addition, ANOVA will be employed to compare, identify, and understand specific factors that significantly impact adolescents’ mental health. The qualitative data will be analysed using Colaizzi’s seven-step framework and will be facilitated with NVIVO 15.